Unusual position of external carotid artery: a case report - S B Rao; V R Vollala; M Rao; V P Samuel; D Deepthinath; S Nayak; N Pamidi (Indian Journal of Plastic Surgery)
The arterial pattern of the human body is one of the systems that show a large number of variations. Many reports are available regarding variations of common carotid, external and internal carotid arteries and branches of external carotid artery. We describe a very rare case of lateral position of external carotid artery. The external carotid artery was lateral to the internal carotid artery at the bifurcation of the common carotid artery. The clinical importance of this variation is discussed.